The effects of an employee fitness program on health care costs and utilization. - Bell BC; Blanke DJ (Health Values: The Journal of Health Behavior, Education & Promotion)
Health care utilization among participants and nonparticipants of an employee fitness program was investigated in a study involving 206 workers at a large transportation company. Health care utilization was measured by hospital days, medical costs, and medical claims over a 16-month period. Female nonparticipants had fewer medical claims, and those 40 years and younger had lower medical costs and medical claims, following the program. Prior to the program, male nonparticipants had significantly lower medical costs and medical claims than did female nonparticipants. Results suggest that significant reductions in health care utilization among fitness center participants may not occur during the early months of program operation.